Learning medical terminology : - Austrin, Miriam G. (Mosby, 1999)
A reliable tool for studying the language of medicine, LEARNING MEDICAL TERMINOLOGY provides a solid foundation for building a complete medical vocabulary. The first four chapters teach the word parts used to build medical terms and explain how to combine them. The remaining fourteen chapters present medical terminology as its relates to the various body systems. The related terms listings in the body systems chapters include anatomic terms, pathologic conditions, surgical procedures, and laboratory tests with pronunications and definitions.